CHILD ABUSE: TYPES, SPECIFIC ACTS AND PREVENTION STRATEGIES - Iyang, Grace Masha; Mayanchi, Mohammed Lawal; Madawaki, A'isha Isah (Sokoto Educational Review, 2020)
Noticeable efforts have begun to emerge from Local, States and Federal Government levels on dealing with issues of child abuse. Perhaps this was as a result of numerous cases of child abuse reported in our daily newspapers. It may also be as a result of various efforts by Non-Governmental Organizations, Human Rights Activities and Community-Based Organization. As part of the contribution to the issue, this paper discusses the child abuse, types, specific acts and preventive strategies. In the paper, the concept of child abuse, definitions of terms and who is child were explained. Critically examined also, were background to the children’s right, basic rights of the child and type of child abuse. Furthermore, emotional and psychological abuse and their effects were highlighted. Strategies to reduce emotional psychological abuse were clearly listed. One of the recommendations was that, community awareness of the importance of healthy parenting practices should be enhanced.